Multicenter study of lumbar discectomy with Barricaid annular closure device for prevention of lumbar disc reherniation in US patients: A historically controlled post-market study protocol. Issue 35 (August 2019) - Strenge, K. Brandon; DiPaola, Christian P.; Miller, Larry E.; Hill, Clint P.; Whitmore, Robert G.
Abstract: Background: Patients with large defects in the annulus fibrosus following lumbar discectomy have high rates of symptomatic reherniation. The Barricaid annular closure device provides durable occlusion of the annular defect and has been shown to significantly lower the risk of symptomatic reherniation in a large European randomized trial. However, the performance of the Barricaid device in a United States (US) population has not been previously reported. Design and methods: This is a historically controlled post-market multicenter study to determine the safety and efficacy of the Barricaid device when used in addition to primary lumbar discectomy in a US population. A total of 75 patients with large annular defects will receive the Barricaid device following lumbar discectomy at up to 25 sites in the US and will return for clinical and imaging follow-up at 4 weeks, 3 months, and 1 year. Trial oversight will be provided by a data safety monitoring board and imaging studies will be read by an independent imaging core laboratory. Patients treated with the Barricaid device in a previous European randomized trial with comparable eligibility criteria, surgical procedures, and outcome measures will serve as historical controls. Main outcomes will include back pain severity, leg pain severity, Oswestry Disability Index, health utility on the EuroQol-5 Dimension questionnaire, complications, symptomatic reherniation, and reoperation. Propensity score adjustment using inverse probability of treatment weighting will be used to adjust for differences in baseline patient characteristics between the US trial participants and European historical controls. Ethics and dissemination: This study was approved by a central institutional review board. The study results of this trial will be widely disseminated at conference proceedings and published in peer-reviewed journals. The outcomes of this study will have important clinical and economic implications for all stakeholders involved in treating patients with lumbar discectomy in the US. Study registration: ClinicalTrials.gov (https://clinicaltrials.gov ): NCT03986580. Level of evidence: 3.